Perbedaan Motivasi Belajar Siswa dengan Menggunakan Model Pembelajaran Konvensional dan Model Pembelajaran Active Learning pada Mata Pelajaran Pendidikan Agama Islam (PAI) - Sri Panca Aryaningsih (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the differences in students’ learning motivation between the use of conventional learning models and active learning models in Islamic Religious Education (PAI) subjects at SMAN 1 Lingsar for tenth-grade students in the 2025/2026 academic year. This research employed a quantitative approach with a quasi-experimental design. Data were collected using a Likert-scale questionnaire. The research sample consisted of 56 students, including 28 students in the control class and 28 students in the experimental class. Data analysis was conducted using the independent sample t-test. The results showed that the data were normally distributed (sig. 0.270 > 0.05) and homogeneous (sig. 0.121 > 0.05). The results of the independent sample t-test indicated a significance value of 0.022 < 0.05. Therefore, it can be concluded that there is a significant difference in students’ learning motivation between the use of conventional learning models and active learning models.